Identification and Molecular Characterization of the Mg(2+) Stimulon of Escherichia coli - Minagawa, Shu (American Society for Microbiology, 2003)
Transcription profile microarray analysis in Escherichia coli was performed to identify the member genes of the Mg(2+) stimulon that respond to the availability of external Mg(2+) in a PhoP/PhoQ two-component system-dependent manner. The mRNA levels of W3110 in the presence of 30 mM MgCl(2), WP3022 (phoP defective), and WQ3007 (phoQ defective) were compared with those of W3110 in the absence of MgCl(2). The expression ratios of a total of 232 genes were <0.75 in all three strains (the supplemental data are shown at http://www.nara.kindai.ac.jp/nogei/seiken/array.html), suggesting that the PhoP/PhoQ system is involved directly or indirectly in the transcription of these genes. Of those, 26 contained the PhoP box-like sequences with the direct repeats of (T/G)GTTTA within 500 bp upstream of the initiation codon. Furthermore, S1 nuclease assays of 26 promoters were performed to verify six new Mg(2+) stimulon genes, hemL, nagA, rstAB, slyB, vboR, and yrbL, in addition to the phoPQ, mgrB, and mgtA genes reported previously. In gel shift and DNase I footprinting assays, all of these genes were found to be regulated directly by PhoP. Thus, we concluded that the phoPQ, mgrB, mgtA, hemL, nagA, rstAB, slyB, vboR, and yrbL genes make up the Mg(2+) stimulon in E. coli.